Suplementasi Asam Lemak Omega-3 dan Vitamin D pada Anak dengan Sistemik Lupus Eritematosus - Fika Linatunnafisah; Trismiyanti; Diana Sunardi (Jurnal Ilmu Kesehatan Indonesia, 2026)
Systemic lupus erythematosus is an autoimmune disease characterized by systemic inflammation involving multiple organs. Omega-3 fatty acid and vitamin D have an immunomodulatory effect and considered to decrease the inflammation. However, the effectivity of omega-3 fatty acid and vitamin D supplementation in pediatric SLE is still inconclusive. A 9-year-6-month-underweight girl with neuropsychiatric, hematology, mucocutaneous, and joint involvement SLE is hospitalized for 15 days. Medical nutrition therapy encompasses the provision of energy tailored to the patient’s requirement according to the RDA, macronutrient administration involving a balanced composition of protein, fat and carbohydrates, as well as the delivery of specific nutrients and micronutrients as recommended. Protein was administered at 10% - 17% of total energy, fat is provided at 30% of total energy, micronutrient supplementation included vitamin A, B, and C according to the RDI. The patient was also provided with daily supplementation of 1000 mg of omega-3 fatty acid and 2000 IU of vitamin D3. During the hospitalization, the patient got improvement of the nutritional intake and reduction of VAS score, without any sign of toxicity. Omega-3 fatty acid and vitamin D supplementation is associated to the improvement of clinical condition in pediatric SLE. Keyword: SLE, omega-3, vitamin D